The functions of N6-methyladenosine modification in lncRNAs - He, Rong-Zhang; Jiang, Jing; Luo, Di-Xian (Genes & diseases, 2020)
Increasing evidence indicates that mRNAs are often subject to posttranscriptional modifications. Among them, N6-methyladenosine (m6A), which has been shown to play key roles in RNA splicing, stability, nuclear export, and translation, is the most abundant modification of RNA. Extensive studies of m6A modification of mRNAs have been carried out, while little is known about m6A modification of long non-coding RNAs (lncRNAs). Recently, several studies reported m6A modification of lncRNAs. In this review, we focus on these m6A-modified lncRNAs and discuss possible functions of m6A modification.